Efficacité autobiographique et mémoire affirmative : nouvelles perspectives pour la recherche-formation - Luiz Artur Dos Santos Cestari (Éducation et Socialisation)
This text discusses the significance of memory to the Formation-Research Movement, with special emphasis on autobiographic efficiency, and draws on the work of Gaston Pineau, Pierre Dominicé and Christine Josso. These authors argue that autobiographical experiences are great shaping forces to people ; however, this approach fails to appreciate the contribution of negative experiences. Therefore, the concept of memory employed by this movement is limited to positive experiences.